The Prevalence of Psychological Distress and Its Relationship to Sleep Quality in Saudi Arabia's General Population During the COVID-19 Pandemic - AlRasheed, Maha M.; Al-Aqeel, Sinaa; Alkadir, Afnan M.; Bin Shuqiran, Khulood; Khurshid, Fowad; AlRasheed, Noura M.; Al-kufeidy, Roua M.; Alhaj, Omar A.; Jahrami, Haitham; BaHammam, Ahmed S. (Frontiers in Psychiatry, 2022)
Background: We aimed to examine the effect of the COVID-19 pandemic and associated mitigation measures on sleep quality and psychological distress in Saudi Arabia. Methods: Subjective sleep quality over the preceding 30 days was measured using the Pittsburgh Sleep Quality Index (PSQI). In addition, Kessler Psychological Distress Scale (K10) was used to assess the psychological distress. Results: The study included 836 participants. The median age was 28 years, 624 (74.64%) were females, and 158 (18.90%) were healthcare workers. Factors associated with poor sleep were recent changes in the sleep habits P= 0.004), anxiety or fear because of coronavirus news on social media P= 0.02), fear because there was no approved drug to treat COVID-19 P= 0.03) and unaware of the presence of chronic diseases P= 0.03). Female gender P= 0.02), fear or anxiety because of coronavirus news on social media P= 0.04), recent change in sleep habits (OR: 1.97 (1.15- 3.39); P=0.01), fear because there is no approved drug to treat COVID-19 P= 0.001), monthly income < 1000 SR P= 0.01), and isolation P= 0.01) were associated with distress. PSQI and K10 scores were significantly correlated P <0.001). Conclusion: Poor sleep and psychological distress are common during the COVID-19 outbreak. Identifying factors associated with poor sleep and psychological distress would help develop specific intervention programs that enhance mental health and sleep quality during pandemics.